Safety, immunogenicity and persistence of immune response to the combined diphtheria, tetanus, acellular pertussis, poliovirus and Haemophilus influenzae type b conjugate vaccine (DTPa-IPV/Hib) administered in Chinese infants - Yanping Li; Rong Cheng Li; Qiang Ye; Changgui Li; You Ping Liu; Xiao Ma; Yanan Li; Hong Zhao; Xiaoling Chen; Deepak Assudani; Naveen Karkada; Htay Htay Han; et al. (Taylor & Francis Group, 2017)
We conducted 3 phase III, randomized, open-label, clinical trials assessing the safety, reactogenicity (all studies), immunogenicity (Primary vaccination study) and persistence of immune responses (Booster study) to the combined diphtheria, tetanus, pertussis, poliomyelitis, and Haemophilus influenzae type b vaccine (DTPa-IPV/Hib) in Chinese infants and toddlers. In the Pilot study (NCT00964028), 50 infants (randomized 1:1) received 3 doses of DTPa-IPV/Hib at 2-3-4 (Group A) or 3-4-5 months of age (Group B). In the Primary study (NCT01086423), 984 healthy infants (randomized 1:1:1) received 3 doses of DTPa-IPV/Hib at 2-3-4 (Group A) or 3-4-5 (Group B) months of age, or concomitant DTPa/Hib and poliomyelitis (IPV) vaccination at 2-3-4 months of age (Control group); 825 infants received a booster dose of DTPa/Hib and IPV at 18-24 months of age (Booster study; NCT01449812). In the Pilot study, unsolicited symptoms were more frequent in Group A (16 versus 1 infant; mostly upper respiratory tract infection and pyrexia); this observation was attributed to an epidemic outbreak of viral infections. Non-inferiority of 3-dose primary vaccination with DTPa-IPV/Hib over separately administered DTPa/Hib and IPV was demonstrated for Group A (primary objective). Similar antibody concentrations were observed in all groups, except for anti-polyribosyl-ribitol phosphate and anti-poliovirus types 1-3 which were higher in DTPa-IPV/Hib recipients. Protective antibody levels against all vaccine antigens remained high until booster vaccination. Three-dose vaccination with DTPa-IPV/Hib had a clinically acceptable safety profile.